Uranium geology of the Middle East and North Africa : resources, exploration and development program - Howari, Fares (Elsevier, 2022)
Uranium Geology of the Middle East and North Africa demonstrates mining potential in the MENA region, with a special interest given to Uranium. The formation and origin of uranium deposits is of interest for uranium exploration and is necessary for the long-term sustainability of nuclear energy production. The book proposes a new classification system built on earlier classification with detailed new maps, explanatory diagrams, cross sections, helpful satellite images, etc. In addition, it explains why the occurrences, depositional and geological environments of uranium in the Middle East and North Africa vary from one country to another. Using various related recognition criteria, the book reports the potential uranium provinces in the Middle East and North Africa countries. The definition of these provinces is based on the existing geologic and tectonic settings, along with geochronological sequences and geochemical characteristics.